Chłodno i rzeczowo. Kazimierz Sarnecki o chorobach na dworze Jana III Sobieskiego - Ślęczka, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
This article addresses the question of illness, as discussed in the writings of Kazimierz Sarnecki, an envoy of Lithuanian Chancellor Karol Stanisław Radziwiłł, residing at King Jan III Sobieski’s court. Sarnecki’s primary task was to take note of all happenings at King Sobieski’s court, focusing mainly on the king’s health, but including also other matters, some of them of little importance. Sarnecki regularly kept Radziwiłł up-to-date through diary entries sent together with a separate cover letter, usually of considerable length. In his diary, Sarnecki detailed the King’s state of health, starting each entry with a short description of what the King was doing and how he felt and only then proceeding to report on other events. Subsequently, he also included information on Queen Maria Kazimiera, the King’s sister Katarzyna Radziwiłłowa née Sobieska (mother of Karol Stanisław), the royal couple’s children (Jakub, Teresa Kunegunda, Aleksander and Konstanty), as well as other members of the court and visitors. He also noted down anecdotes, often loosely connected with medicine. When Kazimierz himself fell seriously ill, he did not seek his patron’s compassion, but assured that despite his illness, he would discharge his duties with the help of third parties, so that Radziwiłł’s interests would not be harmed. His notes are always written in a cold and terse tone, devoid of commentary and empathy. Even those passages which concern him personally are free of emotion.
Cold and Terse. Kazimierz Sarnecki writing about Disease at King John III Sobieski’s Court
Keywords: Jan III Sobieski; Kazimierz Sarnecki; Karol Stanisław Radziwiłł; disease; Polish–Lithuanian Commonwealth; 17th century; diary; choroba; Rzeczpospolita Polska; XVII wiek; diariusz